An international study on teachers' conceptions of learning and teaching and corresponding teacher profiles. (1st September 2020) - Jacobs, Johanna C. G.; Wilschut, Janneke; van der Vleuten, Cees; Scheele, Fedde; Croiset, Gerda; Kusurkar, Rashmi A.
Abstract: Introduction: Teachers' conceptions of learning and teaching (COLT) affect their teaching behaviour. The 18 item COLT instrument has been developed in the Netherlands and comprises three scales, 'teacher centredness', 'appreciation of active learning' and 'orientation to professional practice'. Previously we found five teacher profiles. The aim of this study was to find out if the COLT instrument can be used in an international setting. Methods: Data were collected with the web-based COLT. Cronbach's alphas of the three COLT scales were calculated. Subsequently a cluster analysis was conducted to identify different teacher profiles, followed by a split half validation procedure. Results: Respondents ( n  = 708) worked in 28 countries. Cronbach's alphas were 0.67, 0.54, and 0.66. A six-cluster solution fitted best, based on meaning and explained variance. The sixth teacher profile scored high on 'teacher centredness', average on 'appreciation of active learning' and low on 'orientation to professional practice'. The split half validation resulted in a Cohen's kappa of 0.744. Discussion: Cronbach's alphas indicated acceptable reliablities for all three subscales. The new, sixth profile was labelled 'neo-transmitter'. Conclusion: We found evidence supporting the validity of the use of COLT in an international context and identified a new, sixth teacher profile.